Teaching sound principles about invalidity - Oller, Carlos Alejandro (2011)
One of the aims of introductory logic courses for humanities students is to help them understand the structure of, and the evaluation criteria for, natural language arguments. In order to show that symbolic logic can help students achieve this understanding the relationship between natural language arguments and formal language arguments has to be clearly, and correctly, elucidated. The notions of logical form and formal (in)validity, and their relation with the (in)validity of natural language arguments, are essential for this elucidation. The purpose of this paper is to show and explain the fact that, notwithstanding James W. Oliver and Gerald Massey's warnings concerning invalidity verdicts, wrong conceptions about logic-based methods for determining invalidity of natural language arguments have a residual existence in some presentday introductory logic textbooks.